Pembanterasan jenayah penyeludupan beras : Satu kajian kes Agensi Kawalan Sempadan Malaysia di Rantau Panjang - Nik Mohd Zainordin, Nik Mohd Shazlee (2019)
Rice is the staple food for Malaysians wherein per capita consumption of rice in Malaysia for 2016 was around 78.6 kg. This means that the country needs 2.5 million tons of rice per year. But only 1.2 million tons of rice is grown in Malaysia. Malaysia borders Thailand, which is the world's second leading exporter of rice and among the world's largest rice producers. Smugglers exploit this situation to bring in that commodity into the country and get benefit from it. Kelantan-Thailand border is synonymous with rice smuggling activities. Some say that majority of the residents in Kelantan-Thailand border is involved in smuggling activities. Rantau Panjang is the major border crossing between Malaysia and Thailand for the East Coast of Malaysia. Therefore, the study is conducted with the purpose of identifying the challenges, roles, and responsibilities of AKSEM Rantau Panjang as one of the main border control agencies. There are three primary objectives of this study; (i) to assess the extent of the weakness of AKSEM's human resources in carrying out the tasks and roles of combating rice smuggling in Rantau Panjang; (ii) to identify issues, problems and challenges faced by AKSEM Rantau Panjang in curbing smuggling; and (iii) to suggest solutions to the issues, problems and challenges that arise. This is a qualitative study which uses interview technique as a data collection method. Respondents for this study consist of seven members of AKSEM Rantau Panjang. In addition, nine civilians, who are smugglers, sellers, buyers. and residents, are selected as respondents to get further information related to the study. The findings show that AKSEM Rantau Panjang faces human resources problem, staff integrity, logistics and financial challenges. Moreover, the rice price, the smugglers tactics, the lack of cooperation from the locals, and the physical nature of the border also give challenges to AKSEM Rantau Panjang. This study provides recommendations that are appropriate and relevant for the use of AKSEM Rantau Panjang in particular, and the other agency in general, to always move forward in strengthening land border control in the Malaysia-Thailand border